(untitled) (Fiep Bulletin - online, 2024)
Introduction: Unhealthy behaviors, such as lack of exercise, inadequate nutrition, smoking, and excessive alcohol consumption, play a significant role in health problems and mortality. The pursuit of physical activity is often driven by the need to mitigate the negative health impacts of inactivity. In this context, the physical education professional plays an essential role in promoting people’s health and well-being. Objective: The purpose of this article is to analyze the fundamental role of the physical education professional as a crucial element in the preservation of the health of individuals practicing a physical activity. Methods: This article brings a synthesis, through a narrative review, of the importance of the physical education professional, through searches in the literature on the importance of knowledge and the contribution of the professional to the student. Results: According to the results of the literature searches and in agreement with the theoretical and practical knowledge of the author, it is evident the importance of a professional accompanying the training in an individualized way, so that the objectives can be achieved safely and that can be evidenced in each phase of training. Conclusion: The search for the professional in sports practice ceased to be a way to achieve maximum performance in the activity and became the search for well-executed exercise and health care of individuals.